Modification of a metal structure due to change of use - Gómez, José Luis; Klein, Karin; Montiel, Guillermo (Revista ALCONPAT, 2024)
The purpose of this work is to discuss the modifications made to a metal structure built in 1930, made up of triangular lattice beams supported on 60 cm thick walls and 14 interior metal columns to cover an area of 875 m2 that housed the activities of the central market in the city of Deán Funes. In the 1980s the municipal management proposed its recovery for new sports uses, presenting the structural challenge of eliminating intermediate supports. The project and construction date from that time, and for this reason it is discussed the validity of the concepts and solutions adopted, as well as the importance of a maintenance plan to guarantee the degree of safety of the work.